Pembelajaran Matematika Menggunakan Model Contextual Teaching and Learning (CTL) pada Materi Kubus dengan Konteks Tahu di kelas VIII - Depi Adela Sari; Chika Rahayu; Indah Widyaningrum (Universitas Islam Nahdlatul Ulama Jepara, 2018)
This service uses the Pretest Posttest Design design. The purpose of this service is to determine the effect of contextual teaching and learning (CTL) learning models on student learning outcomes on cube material with the context of tofu in grade VIII? Data collection uses documentation and test methods. The data is processed using the t test statistical test. Based on data analysis, the average value of experimental class students is 83.90 and control class 73.11. From the average value obtained by students, it can be seen that mathematics learning using contextual teaching and learning (CTL) learning models with context knows that it has a positive effect on student learning outcomes on cube material